1980
DOI: 10.1104/pp.66.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Host Recognition in the Rhizobium-Soybean Symbiosis

Abstract: (2,3,10,15,32). In the soybean system, a 120,000 dalton glycoprotein with specificity for D-galactose and N-acetyl-D-galactosamine binds specifically to infective strains of Rhizobium japonicum (2,3,(19)(20)(21). This lectin is found in seeds, leaves, stems, and roots of several varieties of Glycine max (23,26), although it appears to be absent or in very low quantity in a few varieties (26,29). Even with all of the evidence indicating that the lectin specifically binds to R. japonicum, there has been little d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
3

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 12 publications
2
61
3
Order By: Relevance
“…The inocula contained I04 rhizobia/ml, and the data are from 3 experiments. (7) and Chen and Phillips (8) and stand in sharp contrast to earlier reports of strong correlations between the adsorption of rhizobia to host roots and the ability ofthe rhizobia to infect and nodulate (10,11,15,16,22,23). These correlations are most extensive with the fast-growing rhizobia, a group of organisms that differs substantially from the slow-growing strains that infect soybean and cowpea (26).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The inocula contained I04 rhizobia/ml, and the data are from 3 experiments. (7) and Chen and Phillips (8) and stand in sharp contrast to earlier reports of strong correlations between the adsorption of rhizobia to host roots and the ability ofthe rhizobia to infect and nodulate (10,11,15,16,22,23). These correlations are most extensive with the fast-growing rhizobia, a group of organisms that differs substantially from the slow-growing strains that infect soybean and cowpea (26).…”
Section: Resultscontrasting
confidence: 52%
“…and Zucc. ), but cells of nonnodulating Rhizobium strains are reported not to bind to similar roots (22). Certain nonnodulating R. japonicum mutants also apparently fail to bind to soybean roots (23).…”
mentioning
confidence: 99%
“…Many observations have revealed polar attachment of rhizobial cells to plant root surface immediately after inoculation (Napoli et al, 1975;Stacey et al, 1980). Marshall et al (1985) demonstrated the hydrophobicity of rhizobial cell surface to be a cause of the polar orientation of the cells at interface.…”
Section: Resultsmentioning
confidence: 99%
“…Stacey et al (18) demonstrated the presence of a Rhizobium binding lectin on the roots of soybean. Gade et al (12) were able to purify soybean lectin from roots and showed that it had similar properties to the seed lectin.…”
Section: Discussionmentioning
confidence: 99%